IMPROVING STUDENTS’ LEARNING OUTCOME ON HISTORY INSTRUCTION THROUGH GROUP INVESTIGATION LEARNING MODEL - Mahardika, Moch. Dimas Galuh; Agung, Dewa Agung Gede; Utami, Indah Wahyu Puji (Universitas Lambung Mangkurat, 2023)
Poor learning outcomes are often occurred on history instructions at school, including in MAN Kota Batu. Among others, students of X-IPS-1 have the lowest learning outcomes. Their final examination grades on history subject were the lowest among other class. To improve this situation, a Group Investigation learning model was implemented in frame of Classroom Action Research (CAR). In this study, researchers collaborated wirth history teacher of X-IPS-1 MAN Kota Batu in conducting two cycles of CAR including (1) planning, (2) implementation, (3) observation, and (4) reflection. Upon completion of the first cycle, students’ learning outcomes were good with the average grade of 79.31. Further improvement were shown on the following cycle with the average grade of 83.33. The result of this study indicates that Group Investigation model on history instruction could help students on improving their learning outcomes.